Targeting Aspergillus fumigatus Crf Transglycosylases With Neutralizing Antibody Is Relevant but Not Sufficient to Erase Fungal Burden in a Neutropenic Rat Model - Chauvin, David; Hust, Michael; Schütte, Mark; Chesnay, Adélaïde; Parent, Christelle; Moreira, Gustavo Marçal Schmidt Garcia; Arroyo, Javier; Sanz, Ana Belén; Pugnière, Martine; Martineau, Pierre; Chandenier, Jacques; Heuzé-Vourc’h, Nathalie; et al. (Frontiers in Microbiology, 2019)
Aspergillus fumigatus is an airborne opportunistic fungal pathogen responsible for severe infections. Among them, invasive pulmonary aspergillosis has become a major concern as mortality rates exceed 50% in immunocompromised hosts. In parallel, allergic broncho-pulmonary aspergillosis frequently encountered in cystic fibrosis patients, is also a comorbidity factor. Current treatments suffer from high toxicity which prevents their use in weakened subjects, resulting in impaired prognostic. Because of their low toxicity and high specificity, anti-infectious therapeutic antibodies could be a new alternative to conventional therapeutics. In this study, we investigated the potential of Chitin Ring Formation cell wall transglycosylases of A. fumigatus to be therapeutic targets for therapeutic antibodies. We demonstrated that the Crf target was highly conserved, regardless of the pathophysiological context; whereas the CRF1 gene was found to be 100% conserved in 92% of the isolates studied, Crf proteins were expressed in 98% of the strains. In addition, we highlighted the role of Crf proteins in fungal growth, using a deletion mutant for CRF1 gene, for which a growth decrease of 23.6% was observed after 48h. It was demonstrated that anti-Crf antibodies neutralized the enzymatic activity of recombinant Crf protein, and delayed fungal growth by 12.3% in vitro when added to spores. In a neutropenic rat model of invasive pulmonary aspergillosis, anti-Crf antibodies elicited a significant recruitment of neutrophils, macrophages and T CD4 lymphocytes but it was not correlated with a decrease of fungal burden in lungs and improvement in survival. Overall, our study highlighted the potential relevance of targeting Crf cell wall protein with therapeutic antibodies.